Pelatihan dan Sosialisasi Keselamatan Berlalu-lintas di Jalan Raya Pasca Pandemi Covid-19 bagi Siswa SMAN 9 Bandung, Jawa Barat - Atmy Verani Rouly Sihombing; Mulyadi Yuswandono; Aditia Febriansya; Retno Utami; Andri Krisnandi Somantri; Asep Sundara; Hamdan Kurnia; Nadia Azhari Alfiyyati (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Over the past two years, learning activities have been carried out remotely due to the Covid-19 pandemic have limited the movement of students in roads, this has affected the lack of adaptation of students in traffic safety. To prepare students to carry out learning activities at school so that they can more quickly adapt to the current post-pandemic conditions on the roads, education about traffic safety is conducted. Training was carried out at SMA Negeri 9 Bandung, West Java, with the main target being 12th grade (17 years and over) for the category of private motorized vehicle users, students in 10th, 11th, and 12th grades for the category of pedestrians or users of public transportation. In general, students use private vehicles due to the lack of public transportation to the urban area (feeder transportation mode). Besides that, it is also known that there is less-awareness to protect themselves in traffic, such as driving their vehicles exceeding standard speeds, not obeying traffic signs, and so on, caused by a lack of knowledge of traffic safety placing students in a vulnerable to accidents. The results of traffic safety training for high school students show that, after training and outreach, students' knowledge increases by 30%, of which students who travel alone to school increase by 51%, this is strengthened by student knowledge to be able to distinguish between signs and traffic markings which increased by 45% can be used as a provision to be able to adapt in traffic safety on the road.